Comparison of Irisin Serum Healthy Untrained Males on Treadmill Exercises by Increasing Gradually Speed Vs Inclination - Uda'a, Budiyanto; Tinduh, D; Masduchi, HR; Laswati, Laswati; Wibisono, S; Soenatalina, Soenatalina; Theodora, S (Folia Medica Indonesiana, 2020)
Aerobic exercise can improve cardiorespiratory fitness in young people. Irises released into the bloodstream function to execute regulation of energy metabolism, triggering browning white adipose, which is useful in mitochondrial biogenesis. The American College of Sport Medicine (ACSM) recommends moderate intensity cardiorespiratory fitness training with a frequency of 3-5 times a week, duration of 20-60 minutes, using a treadmill. Study subjects (n = 20) were divided randomly into 2 groups, namely the moderate intensity Treadmill training group with gradual speed improvement and gradual inclination increase. Serum slices are measured on the first and last day of exercise. There was an increasing of irisin serum in the moderate intensity Treadmill training group by increasing gradually speed after 2 weeks of exercise, both 30 minutes pre-exercise (p = 0.02) and 1 hour post exercise (p = 0.01). Medium intensity Treadmill training with 2 weeks gradual speed increase with frequency 3 times a week can increase serum slice in men, healthy untrained young men.